THE INFLUENCE OF ROLE PARENTS IN HABITUATION GRADE IV ELEMENTARY SCHOOL STUDENTS IMPLEMENT CLEAN AND HEALTHY BEHAVIOR - Isna Nurazmi; Diki Rukmana (Universitas Majalengka, 2023)
The fact that the educational role of parents is lacking in forming clean and healthy living habits is the background of this research. As subjects of formal education for students, parents must be able to develop practices that prioritize cleanliness and health. During the Covid-19 pandemic, instilling clean and healthy living habits became very important for students in the world of education. The study was conducted by involving fourth-grade elementary school students as participants to determine how effective parents' role was in influencing the development of clean and healthy living habits by using a quantitative cross-sectional design approach based on survey analysis. The research findings show that simple linear regression analysis shows a parental influence coefficient of 1.106 which gives a positive value. The t-test also showed that the parental role variable had a higher t count, namely 17.581, than t table 1.993, along with a Pearson value of 0.902 and a significance value of 0.000, less than 0.05. From the R2 test, parental influence gives a value of 0.813 or 81.3%, and other variables provide a value of 0.187 or 18.7%. Therefore, the conclusion is that the role of parents is very influential and has a strong relationship in forming clean and healthy living habits for fourth-grade elementary school students. Fakta bahwa peran edukatif orang tua yang kurang dalam membentuk kebiasaan hidup bersih dan sehat menjadi latar belakang penelitian ini. Orang tua, sebagai subjek pendidikan formal bagi siswa, harus mampu membentuk kebiasaan yang memprioritaskan kebersihan dan kesehatan. Selama pandemi Covid-19, menanamkan perilaku hidup bersih dan sehat menjadi sangat penting bagi siswa dalam dunia pendidikan. Penelitian dilakukan dengan melibatkan siswa kelas IV sekolah dasar sebagai partisipan untuk mengetahui seberapa efektif peran orang tua dalam mempengaruhi perkembangan kebiasaan hidup bersih dan sehat dengan menggunakan pendekatan kuantitatif desain cross-sectional berbasis analisis survei. Temuan penelitian menunjukkan bahwa analisis regresi linier sederhana menunjukkan koefisien pengaruh orang tua sebesar 1,106 yang memberikan nilai positif. Pada uji t juga dihasilkan bahwa variabel peran orang tua memiliki t hitung lebih besar yaitu 17,581 dari t tabel 1,993 beserta nilai pearson sebesar 0,902 dan nilai signifikansi 0,000 lebih kecil dari 0,05. Dari uji R2 bahwa pengaruh orang tua memberikan nilai sebesar 0,813 atau 81,3%, dan variabel lain memberikan nilai sebesar 0,187 atau 18,7%. Oleh karena itu, kesimpulannya adalah bahwa peran orang tua sangat berpengaruh dan memiliki hubungan yang kuat dalam membentuk kebiasaan hidup bersih dan sehat bagi siswa kelas IV sekolah dasar.